PD-1-expressing macrophages and CD8 T cells are independent predictors of clinical benefit from PD-1 inhibition in advanced mesothelioma - Solange Peters; Urania Dafni; Panagiota Zygoura; Sanjay Popat; Mary O'Brien; Rolf A Stahel; Alessandra Curioni-Fontecedro; Georges Coukos; Amy Roy; Riyaz Shah; Krisztian Homicsko; James Spicer; et al. (Journal for ImmunoTherapy of Cancer)
Background Few tissue biomarkers exist to date that could enrich patient with cancer populations to benefit from immune checkpoint blockade by programmed cell death protein 1/ligand-1 (PD-/L-1) inhibitors. PD-L1 expression has value in this context in some tumor types but is an imperfect predictor of clinical benefit. In malignant pleural mesothelioma, PD-L1 expression is not predictive of the benefit from PD-1 blockade. We aimed to identify novel markers in malignant pleural mesothelioma to select patients better.Methods We performed a multiplex-immune histochemistry analysis of tumor samples from the phase III PROMISE-meso study, which randomized 144 pretreated patients to receive either pembrolizumab or standard second-line chemotherapy. Our panel focused on CD8+T cell, CD68+macrophages, and the expression of PD-1 and PD-L1 on these and cancer cells. We analyzed single and double positive cells within cancer tissues (infiltrating immune cells) and in the stroma. In addition, we performed cell neighborhood analysis. The cell counts were compared with clinical outcomes, including responses, progression-free and overall survivals.Results We confirmed the absence of predictive value for PD-L1 in this cohort of patients. Furthermore, total CD8 T cells, CD68+macrophages, or inflammatory subtypes (desert, excluded, inflamed) did not predict outcomes. In contrast, PD-1-expressing CD8+T cells (exhausted T cells) and PD-1-expressing CD68+macrophages were both independent predictors of progression-free survival benefit from pembrolizumab. Patients with tumors simultaneously harboring PD1+T cells and PD-1+macrophages benefited the most from immune therapy.Conclusion We analyzed a large cohort of patients within a phase III study and found that not only PD-1+CD8 T cells but also PD-1+CD68+ macrophages are predictive. This data provides evidence for the first time for the existence of PD-1+macrophages in mesothelioma and their clinical relevance for immune checkpoint blockade.